DTI-based tractographic analysis of white matter alterations in HIV infected children - Madzime, Joanah (Division of General Surgery, 2020)
Despite early combination antiretroviral therapy (cART) administration, children born with human immunodeficiency virus (HIV) continue to demonstrate neurodevelopmental abnormalities. Often, there is a link between structural and functional abnormalities. Previously, we found HIV-associated changes in white matter and functional networks in a cohort of 7-year-old HIV infected (HIV+) children who intiatied early cART compared to uninfected controls. To explore possible relationships between these alterations, we used tractography to identify HIV-related abnormalities within structural connections located in functional resting state networks. Within HIV+ children (n=61), we identified white matter (WM) tracts with lower mean fractional anisotropy (FA) and/or higher mean diffusivity (MD) located in several functional networks, including the somatosensory, auditory, salience, default mode network (DMN), motor and basal ganglia networks compared to uninfected controls (n=46). Among the uninfected controls, children born to HIV+ mothers (exposed uninfected, HEU) (n=19) showed WM alterations (higher FA) compared to HIV unexposed uninfected children (HUU) (n=27) within tracts in the posterior DMN, visual (occipital lobe and lingual gyrus), salience and motor networks. The observed WM alterations in HIV+ children point to demyelination/dysmyelination within six networks. Four of these networks – the basal ganglia, default mode, salience and somatosensory – were all found to have altered functional connectivity in a previous study; therefore, these results point to damage or developmental delay in white matter may be related to or responsible for the HIV-associated functional abnormalities. The observed WM alterations in the HEU children suggest that even exposure to HIV and/or antiretroviral therapy (ART) also has long-term effects on axonal integrity in the developing brain.